Efficacy of depatuxizumab mafodotin (ABT-414) monotherapy in patients with EGFR-amplified, recurrent glioblastoma: results from a multi-center, international study - van den Bent, Martin (Cancer Chemother Pharmacol, 2017)
PURPOSE: Patients with recurrent glioblastoma (rGBM) have a poor prognosis. Epidermal growth factor receptor (EGFR) gene amplification is present in ~ 50% of glioblastomas (GBMs). Depatuxizumab mafodotin (depatux-m), formerly ABT-414, is an antibody–drug conjugate that preferentially binds cells with EGFR amplification, is internalized and releases a potent antimicrotubule agent, monomethyl auristatin F (MMAF). Here we report the safety, pharmacokinetics, and efficacy of depatux-m monotherapy at the recommended Phase 2 dose (RPTD) in patients with EGFR-amplified, rGBM. METHODS: M12-356 (NCT01800695) is an open-label study with three escalation and expansion cohorts. Sixty-six patients with EGFR-amplified, rGBM were treated with depatux-m monotherapy at 1.25 mg/kg intravenously every 2 weeks. Adults with measurable rGBM, who were bevacizumab-naïve, with EGFR amplification were eligible. RESULTS: Among 66 patients, median age was 58 years (range 35–80). All patients were previously treated with radiotherapy/temozolomide. The most common adverse events (AEs) were eye related (91%), including blurred vision (65%), dry eye (29%), keratitis, and photophobia (27% each). Grade 3/4 AEs occurred in 42% of all patients, and ocular Grade 3/4 AEs occurred in 33% of patients overall. One patient (2%) had a Grade 4 ocular AE. Ocular AEs were manageable and usually resolved once treatment with depatux-m ceased. The objective response rate was 6.8%, the 6-month progression-free survival rate was 28.8%, and the 6-month overall survival rate was 72.5%. CONCLUSION: Depatux-m monotherapy displayed frequent but mostly Grade 1/2 ocular toxicities. A PFS6 of 28.8% was observed in this rGBM population, warranting further study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00280-017-3451-1) contains supplementary material, which is available to authorized users.